Molecular Cytogenetic Analysis of One African and Five Asian Macaque Species Reveals Identical Karyotypes as in Mandrill - Sangpakdee, Wiwat; Tanomtong, Alongkoad; Chaveerach, Arunrat; Pinthong, Krit; Trifonov, Vladimir; Loth, Kristina; Hensel, Christiana; Liehr, Thomas; Weise, Anja; Fan, Xiaobo (Current Genomics, 2018)
Background: The question how evolution and speciation work is one of the major interests of biology. Especially, genetic including karyotypic evolution within primates is of special interest due to the close phylogenetic position of Macaca and Homo sapiens and the role as in vivo models in medical research, neuroscience, behavior, pharmacology, reproduction and Acquired Immune Deficiency Syndrome (AIDS). Materials & Methods: Karyotypes of five macaque species from South East Asia and of one macaque species as well as mandrill from Africa were analyzed by high resolution molecular cytogenetics to obtain new insights into karyotypic evolution of old world monkeys. Molecular cytogenetics applying human probes and probe sets was applied in chromosomes of Macaca arctoides, M. fascicularis, M. nemestrina, M. assamensis, M. sylvanus, M. mulatta and Mandrillus sphinx. Established two- to multicolor- fluorescence in situ hybridization (FISH) approaches were applied. Locus-specific probes, whole and partial chromosome paint probes were hybridized. Especially the FISH-banding approach multicolor-banding (MCB) as well as probes oriented towards heterochromatin turned out to be highly efficient for interspecies comparison. Conclusion: Karyotypes of all seven studied species could be characterized in detail. Surprisingly, no evolutionary conserved differences were found among macaques, including mandrill. Between the seven here studied and phenotypically so different species we expected several via FISH detectable karyoypic and submicroscopic changes and were surprised to find none of them on a molecular cytogenetic level. Spatial separation, may explain the speciation and different evolution for some of them, like African M. sylvanus, Mandrillus sphinx and the South Asian macaques. However, for the partially or completely overlapping habitats of the five studied South Asian macaques the species separation process can also not be deduced to karyotypic separation.
Keywords: Mandrillus sphinx